Thread bonds in molecules - Ivlev, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Unusual chemical bonds are proposed. Each bond is characterized by the thread of a small radius, 10–11 cm,extended between two nuclei in a molecule. An analogue of a potential well, of the depth of MeV scale, is formed within the thread. This occurs due to the local reduction of zero point electromagnetic energy. This is similar to formation of the Casimir well. The electron–photon interaction only is not sufficient for formation of thread state. The mechanism of electron mass generation is involved in the close vicinity, 10–16 cm, of thethread. Thread bonds are stable and cannot be created or destructed in chemical or optical processes.